The igloo - Yue, Charlotte; Yue, David (Boston : Houghton Mifflin Co., 1988)
Describes how an igloo is constructed and the role it plays in the lives of the Eskimo people. Also discusses many other aspects of Eskimo culture that have helped them adapt to life in the Arctic.
The people and the land -- The igloo -- Living in an igloo -- Snow villages -- Traveling in the Arctic -- Other kinds of Eskimo houses -- Eskimos today.
Includes bibliographical references (p. 111-113) and index.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
6.1
6.1
Keywords: Eskimos -- Dwellings -- Juvenile literature; Igloos -- Juvenile literature; Indians of North America -- Dwellings -- Juvenile literature; Eskimos -- Dwellings; Igloos; Indians of North America -- Dwellings; Igloos; Inuit -- Dwellings; Native Americans -- Dwellings -- North America